Analysis Translation Techniques of Cultural Term from Indonesian to Mandarin Case Study: Five Priority Destinations - Amelia, Husnul Rieski; Suyudi, Ichwan; Pasang, Kezia Yansen (Institut Agama Islam Negeri Palopo, 2023)
The purpose of this study is to describe the types of cultural terms contained in the Woderful Indonesia web article with case studies of five super priority destinations and to describe the translation techniques used in translating Indonesian cultural terms into Mandarin. The object of this research is an article containing five super-priority destinations in the Indonesian version and the Chinese equivalent from the Wonderful Indonesia website. The five priority destinations are Lake Toba, North Sumatra; Borobudur, Central Java; Mandalika-Lombok, West Nusa Tenggara; Labuan Bajo, East Nusa Tenggara; Likupang, North Sulawesi. This study uses a qualitative descriptive approach with data collection techniques, namely the study of documentation. Words containing cultural terms were analyzed using Newmark's theory (1988) and translation techniques using the theory of Molina and Albir (2002). The results showed that there were five categories of cultural terms used, namely the category of ecology, material culture, socio-culture, social organization, politics, and administration, body language and habits. For the translation techniques used, 14 techniques were found, namely adaptation, amplification, pure borrowing, naturalized translation, kalke, compensation, description, Estabilished equivalence, generalization, linguistic amplification, literal, modulation, particulation, reduction, and transposition.